Barium‐Catalysed Dehydrocoupling of Hydrosilanes and Borinic Acids: A Mechanistic Insight. Issue 16 (21st February 2020) - Le Coz, Erwann; Zhang, Ziyun; Roisnel, Thierry; Cavallo, Luigi; Falivene, Laura; Carpentier, Jean‐François; Sarazin, Yann
Abstract: Two very rare cases of barium boryloxides, the homoleptic [Ba(OB{CH(SiMe3 )2 }2 )2 ⋅C7 H8 ] and the heteroleptic [LO NO4 BaOB{CH(SiMe3 )2 }2 ] stabilised by the multidentate aminoetherphenolate LO NO4 −, are presented, and their structural properties are discussed. The electron‐deficient [Ba(OB{CH(SiMe3 )2 }2 )2 ⋅C7 H8 ] shows, in particular, resilient η 6 ‐coordination of the toluene molecule. Together with its amido parents [Ba{N(SiMe3 )2 }2 ⋅thf2 ] and [Ba{N(SiMe3 )2 }2 ]2, this complex catalyses the fast and chemoselective dehydrocoupling of borinic acids R2 BOH and hydrosilanes HSiR′3, yielding borasiloxanes R2 BOSiR′3 in a controlled fashion. The assessment of substrate scope indicates that, for now, the reaction is limited to bulky borinic acids. Kinetic analysis shows that the rate‐limiting step of the catalytic manifold traverses a dinuclear transition state. A detailed mechanistic scenario is proposed on the basis of DFT computations, the results of which are fully consistent with experimental data. It consists of a stepwise process with rate‐determining nucleophilic attack of a metal‐bound O‐atom onto the incoming hydrosilane, involving throughout dinuclear catalytically active species. Abstract : When barium and boron meet : The mechanism of the barium‐mediated dehydrocoupling of borinic acids and hydrosilanes, yielding borasiloxanes in a controlled fashion, has been established by combined experimental and computational investigations.